2020
DOI: 10.1186/s13014-020-01646-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of recombinant human endostatin combined with radiotherapy or chemoradiotherapy in patients with locally advanced non-small cell lung cancer: a pooled analysis

Abstract: Purpose: To assess the efficacy and safety of recombinant human endostatin in combination with radiotherapy (RT) or concurrent chemoradiotherapy (CCRT) in patients with locally advanced non-small cell lung cancer (LA-NSCLC). Methods: We searched eligible literature in available databases using combinations of the following search terms: lung cancer, endostatin or endostar, radiotherapy or radiation therapy or chemoradiotherapy. The inclusion criteria were: prospective or retrospective (including single-arm) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In terms of the safety, we found that Endostar plus CCRT was an independent risk factor for neutropenia and infection. Similarly, it was once reported that a higher incidence of neutropenia occurred in locally advanced NSCLC when combined with Endostar (23). The high frequency of infection could be due to neutropenia, as there is a potential connection between AEs.…”
Section: Discussionmentioning
confidence: 82%
“…In terms of the safety, we found that Endostar plus CCRT was an independent risk factor for neutropenia and infection. Similarly, it was once reported that a higher incidence of neutropenia occurred in locally advanced NSCLC when combined with Endostar (23). The high frequency of infection could be due to neutropenia, as there is a potential connection between AEs.…”
Section: Discussionmentioning
confidence: 82%
“…The incidence of grade 3 or 4 leukopenia in CCRT + E is highly variable across studies, ranging from 5.3 to 44.8% [15,[34][35][36], which may be related to different chemotherapy regimens and cycles, Endostar cycles, and radiotherapy doses. In this study, the incidence of grade 3/4 leukopenia in the CCRT + E group was 32.6%, but all patients recovered with symptomatic management, and no patient interrupted or discontinued treatment, and no patient died of acute toxic events.…”
Section: Discussionmentioning
confidence: 99%
“…e standard treatment is 4-6 cycles of platinum combined with the third generation of cytotoxic drugs. e effective rate is 20.00%-30.00% [2].…”
Section: Introductionmentioning
confidence: 96%
“…The standard treatment is 4–6 cycles of platinum combined with the third generation of cytotoxic drugs. The effective rate is 20.00%–30.00% [ 2 ]. The median survival time is 8–10 months, and the time of disease progression is 3–5 months.…”
Section: Introductionmentioning
confidence: 99%